The Creation of an Experimental Camp of Protohistory at the Iberian Settlement of Estinclells (Verdú, Urgell, Catalonia) - Jordi Morer De Llorens; Ramon Cardona Colell; Conxita Ferrer Alvarez; Cristina Garcia Dalmau; Josep Pou Vallès; David Asensio i Vilaró; Oriol Saula i Briansó; Natàlia Alonso Martínez (EXARC Journal)
The idea to create the Experimental Camp of Protohistory (CEP) emerged in late 2009. It was set up in a field adjacent to the Iberian Culture settlement of Estinclells (Verdú, Urgell), an archaeological site with only one phase of occupation that offers an exceptional portrait of life in the third century BC. The aim of the camp is to concentrate the main lines of Protohistoric experimental research in a single space. These lines include construction, agriculture and processing products. A special emphasis is placed on production of olive oil, livestock and the manufacture of pottery.